Pengaruh Corporate Governance, Sustainability Committee, dan Degree of Multinational Activity Terhadap CSR Disclosure - M. Roif Muntaha; Slamet Haryono (Universitas Wahid Hasyim, 2021)
This study aims to analyze corporate governance, sustainability committee, and degree of multinational activity (DMA) on CSR disclosure. The sample used is 40 companies listed on Jakarta Islam Index (JII) and FTSE Bursa Malaysia Hijrah Shariah Index (FBHMI) for period 2015-2019. The methodology used panel data regression. The results showed that board meetings, size audit committee, women on board and the degree of multinational activity (DMA) affect have a positive effect on CSR disclosure. Meanwhile, board age, CEO duality, CSR training, board independence and sustainability committee have no positive effect on CSR disclosure. Key words : Corporate governance, sustainability committee, degree of multinational activity, CSR disclosure